Proper Nutrition Fuels the Eagle Vision Archers (International Journal of Food and Nutritional Sciences, 2023)
It’s pretty hard to hit a target that you can’t see so it is essential for archers to take care of our vision. Vision is the most dominant sense with 70% of all sensory receptors in the eye. The involvement of vision in archery is paramount importance. Sports vision is concerned with visual abilities needed for recreated and competitive sports, as well as strategies for improving accuracy, consistency and stability in order to improve performance. The visual skills that are important in archery are visual acuity, eye-hand coordination and central peripheral awareness. Nutrition plays a consequential role in visual functioning in archers. It is thus necessary to scrutinize the nutritional advantage of visual performance in archers for better results. All previously published articles and diet plan for archers must be reviewed to correlate the nutritional benefits on visual performance in archers. Reviewing will make it clear that good nutrition, specifically high levels of lutein, zeaxanthin and meso-zeaxanthin, three carotenoids macular pigment found in the macula, have measurable effects on visual function, which may lead to improvements in on-field performance. Vision has the potential to affect your performance including clarity of sight, ability to perform specific tasks, and how you process and respond to what you see on the field. Everyone can benefit from good and proper nutrition because healthy living is better living. Proper nutrition is important also in archers, even though it doesn’t require the same energy level like other sports. But there is physical and mental exertion in archery. For both physical and mental focus, a balanced diet should include carbohydrates, proteins, healthy fats, minerals and vitamins and Studies have found that athletes who don’t drink enough can see as much as a 30-percent reduction in performance.